Resistansi terhadap Objectification dalam Novel Mash-Up "Pride and Prejudice and Zombies" dari Novel Klasik "Pride and Prejudice" - Cindy Belinda Ramadhanty (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This study deals with objectification, especially towards Elizabeth Bennet (Lizzy), in the classic novel Pride and Prejudice (1813) and the mash-up novel Pride and Prejudice and Zombies (2009) which were written by Jane Austen and Seth Grahame-Smith. This study aims to examine how the resistance towards objectification is pictured in the mash-up novel Pride and Prejudice and Zombies using Nussbaum’s theory of objectification. As a comparative study, there are some things that will be compared in this study, such as the different time period when both novels were first published, the way the authors pictured objectification, and the addition of zombie in the mash-up novel Pride and Prejudice and Zombies. This study uses qualitative method with comparative literature as the approach. The result of this study concludes that Lizzy is objectified by Mr. Collins in terms of instrumentality, fungibility, ownership, and denial of subjectivity. The addition of zombie in the mash-up novel Pride and Prejudice and Zombies implies as if there is a resistance towards objectification, with Lizzy having the skills of a warrior, while in fact the objectification is real as experienced by Lizzy. In the perspective of comparative literature, mash-up novel Pride and Prejudice and Zombies tends to have ambivalence even though it is published in postmodern era. On one hand, Lizzy is able to defend herself from zombie, on the other hand, she still falls victim to the objectification done by Mr. Collins. In other words, the resistance towards objectification in the mash-up novel Pride and Prejudice and Zombies is not able to protect Lizzy from the objectification done by Mr. Collins.